MEASUREMENTS ANALYSIS OF MQ-6 LPG GAS LEAK DETECTION DEVICES FOR DISTANCE FACTORS - Sujiwa, Akbar; Prasetyo, Hadi Pri (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2020)
LPG (Liquified Petroleum Gas) is one of the important sources of energy. When compared with other fuels such as oil or firewood, LPG is very practical to be used for household because the material is produced from gas. But behind its practicality, it turns out that LPG gas can cause a danger if not used carefully. According to statistics, the second position of causing fire is a leaky gas cylinder that was ignited by a fire source. To overcome this problem, there a lot of research that uses special tools that can be used to detect leaks for LPG. In the design of the tool, most researchers used MQ-6 type sensors that were indeed built to utilize LPG gas. But studies on the characteristics of MQ-6 have not been done much, especially about the sensitivity of this sensor when used to detect LPG gas at a certain distance, so it needs to be researched about sensor placement. Therefore, in this study the sensitivity testing of the MQ-6 sensor was carried out. The results obtained at a distance of 10 to 30 cm, this sensor is very sensitive in detecting the presence of gas, but at a distance of 30 to 110 cm, it is less sensitive to detect presence of LPG gas because it can only support 10% of the total amount of gas in the air at a distance of 110 cm.